2018
DOI: 10.4254/wjh.v10.i12.924
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and its effects on liver fat content in overweight and obese young adults by proton magnetic resonance spectroscopy technique

Abstract: AIMTo assess the association between liver fat content (LFC) and weight status in young adults using proton magnetic resonance spectroscopy (1H MRS) technique.METHODSSeventy-eight healthy young adults, between 19-30 years of age participated in this study. This group was then separated into a control of 39 subjects and an overweight/obese group (OW/OB group) consisting of 39 subjects. Blood biochemical quantity and 1H MRS was performed for LFC assessment.RESULTSLFC was found to be almost three times higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
4
18
0
Order By: Relevance
“…One of the interesting and reassuring findings from the current study is that BMI and waist circumference (among others) are independent predictors of fatty liver disease in agreement with previous studies ( 25 , 26 ). In fact, Mansour et al ( 27 ) further found that waist circumference was independently associated with liver fibrosis with OR 1.15, 95% CI 1.05–1.25.…”
Section: Discussionsupporting
confidence: 92%
“…One of the interesting and reassuring findings from the current study is that BMI and waist circumference (among others) are independent predictors of fatty liver disease in agreement with previous studies ( 25 , 26 ). In fact, Mansour et al ( 27 ) further found that waist circumference was independently associated with liver fibrosis with OR 1.15, 95% CI 1.05–1.25.…”
Section: Discussionsupporting
confidence: 92%
“…Obesity is one of the world’s leading health problems (Abdou, Magour & Mahmoud, 2009; Dietz, 2017; Hruby & Hu, 2015; Pasanta et al, 2018; Ramachandran & Snehalatha, 2010), and it reduces the quality of life and health for people affected by it. Obesity has been directly associated with 3.4 million deaths each year and is associated with a higher risk of non-communicable diseases such as cardiovascular disease, diabetes, and certain kinds of cancer (Anstee, Targher & Day, 2013; Berger, 2018; Hu et al, 2001; Lim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Six resonances of fat are usually detected with the main lipid peak at approximately 0.9 to 2.75 ppm. There are also unresolved fat resonances at 4.2 and 5.3 ppm from glycerol and olefinic acid, respectively ( Figure 2 ) [ 73 , 74 , 75 ]. These two peaks overlap with the water peak signal at 4.7 ppm.…”
Section: Basic Principle For Mrsmentioning
confidence: 99%
“…This illustrates the feasibility of MRS for hepatic steatosis grading in the general population. Due to the increasing prevalence of obesity worldwide, MRS has been used to assess liver fat in obese patients, type 2 diabetes (T2D) patients, and patients at risk of fatty liver [ 75 , 93 , 94 , 95 ]. Furthermore, MRS has been used to evaluate liver health assessment recommendations for T2D patients at risk of liver steatosis [ 96 ].…”
Section: Application Of Mrs For Liver Fat Quantificationmentioning
confidence: 99%
See 1 more Smart Citation